Information Technology Enterprise Architecture Planning in the National and Political Unity Agency “KESBANGPOL” of Salatiga City Using Enterprise Architecture Planning (EAP) - Chevin Robert Warint; Yani Rahardja; Melkior N. N Sitokdana (TEPIAN, 2020)
The National and Political Unity Agency "KESBANGPOL" of Salatiga City is a government agency tasked with overseeing community activities in Salatiga City. In designing the information system architecture of the National Unity and Political Body "KESBANGPOL" of Salatiga City, the Enterprise Architecture Planning "EAP" methodology is used. Enterprise Architecture Planning "EAP" is a tool developed to build an enterprise architecture that harmonizes the three types of architecture in its development, namely data architecture, application architecture, and technology architecture. Based on this research it was found that there was no adequate administrative information system. The condition of the computer network owned by The National and Political Unity Agency "KESBANGPOL" has 1 internet-connected to 1 server. 1 The server is connected to 2 Routers, where 2 Routers are connected to 23 PC Servers and also connected to 20 printers. Based on the application system architecture, the mapping process of infrastructure components can be carried out. These infrastructure facilities are still inadequate for The National and Political Unity Agency "KESBANGPOL" with community service activities in Salatiga City which are very dense, so it is necessary to add computer and PC networks in order to facilitate service activities.